Increased glomerular filtration rate and impaired contractile function of mesangial cells in TRPC6 knockout mice - Weizu Li (Nature Portfolio, 2017)
Abstract The present study was conducted to determine if TRPC6 regulates glomerular filtration rate (GFR) and the contractile function of glomerular mesangial cells (MCs). GFR was assessed in conscious TRPC6 wild type and knockout mice, and in anesthetized rats with and without in vivo knockdown of TRPC6 in kidneys. We found that GFR was significantly greater, and serum creatinine level was significantly lower in TRPC6 deficient mice. Consistently, local knockdown of TRPC6 in kidney using TRPC6 specific shRNA construct significantly attenuated Ang II-induced GFR decline in rats. Furthermore, Ang II-stimulated contraction and Ca2+ entry were significantly suppressed in primary MCs isolated from TRPC6 deficient mice, and the Ca2+ response could be rescued by re-introducing TRPC6. Moreover, inhibition of reverse mode of Na+-Ca2+ exchange by KB-R7943 significantly reduced Ca2+ entry response in TRPC6-expressing, but not in TRPC6-knocked down MCs. Ca2+ entry response was also significantly attenuated in Na+ free solution. Single knockdown of TRPC6 and TRPC1 resulted in a comparable suppression on Ca2+ entry with double knockdown of both. These results suggest that TRPC6 may regulate GFR by modulating MC contractile function through multiple Ca2+ signaling pathways.